2017
DOI: 10.1016/j.ssi.2017.02.005
|View full text |Cite
|
Sign up to set email alerts
|

All-solid-state flexible nanocomposite polymer electrolytes based on poly(ethylene oxide): Lithium perchlorate using functionalized graphene

Abstract: Solid polymer electrolytes (SPEs) rapidly attracted a great attention as a potential material to be used in flexible rechargeable lithium ion batteries, if an optimal match between their ionic conductivity and mechanical stability was achieved. In this work, two types of nanocomposite SPE based on poly(ethylene) oxide (PEO) and lithium perchlorate salt (LiClO 4) containing pristine graphene (GnP) or polyethylene glycol-grafted graphene (FGnP) were prepared. Differential scanning calorimetry (DSC) and X-ray dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 60 publications
3
30
0
Order By: Relevance
“…It was concluded here that the natural HNT clay mineral provides the desirable energy density at low cost with improved safety. Gomari et al, [70] reported the preparation of nanocomposite solid polymer electrolyte based on poly(ethylene) oxide (PEO) and lithium perchlorate salt (LiClO4) with pristine graphene (GnP) or polyethylene glycol-grafted graphene (FGnP). From FESEM analysis of the nanocomposite, it was concluded that the rough surface of the pristine PEO changes to smooth on the addition of GnP/FGnP and suggests the better dispersion of both.…”
Section: Nanoclay Dispersed Polymer Nanocompositesmentioning
confidence: 99%
“…It was concluded here that the natural HNT clay mineral provides the desirable energy density at low cost with improved safety. Gomari et al, [70] reported the preparation of nanocomposite solid polymer electrolyte based on poly(ethylene) oxide (PEO) and lithium perchlorate salt (LiClO4) with pristine graphene (GnP) or polyethylene glycol-grafted graphene (FGnP). From FESEM analysis of the nanocomposite, it was concluded that the rough surface of the pristine PEO changes to smooth on the addition of GnP/FGnP and suggests the better dispersion of both.…”
Section: Nanoclay Dispersed Polymer Nanocompositesmentioning
confidence: 99%
“…Nevertheless, it is difficult to greatly increase the mechanical strength by using the nanofillers for commercial applications due to the failure of forming interconnected reinforcements [3,26]. Moreover, the room-temperature ion conductivity cannot be greatly improved, because of the low dispersity of the high-surface-area nanofillers, poor interactions between the nanofiller and the electrolyte matrices, and short ion transport pathways between the nanofiller/polymer-Li salt interfaces [13,25,[27][28][29]. To address these issues, constructing special CPEs by filling the SPEs in porous inorganic films as three-dimensional (3D) scaffolds has been reported to significantly enhance the thermal stability, electrochemical window and ionic conductivity [30][31][32][33][34][35][36]; however, there are few reports on the mechanical properties of these CPEs and the cycling performance of the CPE-based all-solid-state batteries, possibly due to the high stiffness/brittleness of the ceramic scaffolds.…”
Section: Introductionmentioning
confidence: 99%
“…They suggested that NPs acted as a multifunctional component in the GPE. In a very recent study, Gomari et al [ 29 ] pioneeringly grafted poly ethylene glycol (PEG) onto graphene and employed it in a PEO electrolyte to enhance ionic conductivity through lowering the nanocomposite crystallinity. According to their results, PEG-grafted graphene was achieved through hydrogen bonding with oxygen atoms of PEO chains, possibly deteriorating the crystallinity of the PEO-based electrolyte.…”
Section: Introductionmentioning
confidence: 99%